DIGITALISASI PROMOSI DAN EDUKASI TRANSAKSI NIRTUNAI (QRIS) PADA UMKM DESA PEDATARAN MELALUI KONTEN VIDEO PENDEK TIKTOK - Oktaviana, Nova; Armasito Armasito (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of digital technology offers great opportunities for Micro, Small, and Medium Enterprises (MSMEs) in rural areas to expand their market reach. However, limited digital literacy often causes business actors to not optimize social media as a marketing instrument. This community service activity aims to help digitalize promotion while educating the public regarding cashless payment methods (QRIS) at the